Linkage among Two Satellite Cities: What makes People Move? (Case Study: Bogor Regency and Depok City) - Wijayanti, Wawargita Permata; Machmud, Sulthon Kamel; Subagiyo, Aris (Perencanaan Wilayah dan Kota FT UB, 2023)
An interaction between cities around metropolitan system occurs due to the limitless of infrastructures, demand of goods-jobs, and others. This case occurs in Bogor Regency and Depok City, as secondary or satellite cities of Jabodetabekpunjur Area. Exchanges of people, goods, and infrastructures among those areas show essential elements of linkages, reflecting three of seven types of linkages. This research examines the factors that influence the linkage among Bogor Regency and Depok City. Besides, it also comprises a relationship between those influential factors and reason of each interaction. We used a factor analysis and cross-tabulation technique to answer those two research objectives. The results show that time, road, consumption and expenditure pattern, regular needs, and use of facilities are crucial factors influencing interaction among the areas. In addition, analysis also reflect that there is a high connection among distance and income to the linkages of the cities. With these findings, this research would contribute not only to enrich on-going discussion related to types of interaction among cities in metropolitan area, but also give empirical evidence about how the balance interaction among cities, which underlines sustainability of regional system occurs.